PENGALAMAN KOMUNIKASI ORANG TUA DALAM MENDIDIK KARAKTER ANAK DI ERA GLOBAL ( STUDI FENOMENOLOGI PADA ORANG TUA GENERASI MILENIAL DI KOTA PEKALONGAN ) - Arham Syarif, Muhamad; Noor Rakhmad, wiwid; Ratri Rahmiaji, Lintang (Interaksi Online, 2024)
Child's moral education is very important in the era of technological battles, different from the character education whose nature is more diverse depending on the nature of the environment.The impact of globalization has become very diverse especially on the pattern of communication between generations namely millennial generation and alpha generation.The most felt impact is that these two generations often choose a way of communicating indirectly i.e. by using gadgets that then make the relationship between both as a child and parents impressed far away. The presence of gadgets as a means of communication also makes these two generations have different communication experiences with other generations, This research aims to know the communication of parents in educating children's character in a global era that focuses on millennial generation parents in shelter cities. The research results show that there are two characters that can be implemented through communication between parents and children. These two characters are a religious character and an honest character. Intense and open communication is carried out by parents to implement religious character and honest character. The communication carried out is realized in communicating directly and indirectly using gadgets. The task of parents in implementing character education is to try to build good communication with their children so that the advice given can be accepted and implemented by their children. The process of giving advice is carried out through direct communication or indirect communication using a cellphone to make it easier to communicate anytime, anywhere. The process of providing advice through communication is also carried out using a special method for one of the informants. The method used is a way of communicating that tends to be full of laughter, not tense and adapted to the family's conditions at that time so that the message or advice conveyed through the communication process can be digested optimally and without coercion. The communication process in an effort to instill character education is also carried out by providing continuous advice when communicating with children. Parents also provide direct examples to their children to support the advice they have been given regarding practicing worship, and telling the truth which can be used as a habit for children to continue to have a positive attitude.